The methodological quality of systematic reviews on the treatment of adult major depression needs improvement according to AMSTAR 2: A cross-sectional study. Issue 9 (September 2020) - Matthias, Katja; Rissling, Olesja; Pieper, Dawid; Morche, Johannes; Nocon, Marc; Jacobs, Anja; Wegewitz, Uta; Schirm, Jaqueline; Lorenz, Robert C.
Abstract: Background: Several standards have been developed to assess methodological quality of systematic reviews (SR). One widely used tool is the AMSTAR. A recent update - AMSTAR 2 - is a 16 item evaluation tool that enables a detailed assessment of SR that include randomised (RCT) or non-randomised studies (NRS) of healthcare interventions. Methods: A cross-sectional study of SR on pharmacological or psychological interventions in major depression in adults was conducted. SR published during 2012–2017 were sampled from MEDLINE, EMBASE and the Cochrane Database of SR. Methodological quality was assessed using AMSTAR 2. Potential predictive factors associated with quality were examined. Results: In rating overall confidence in the results of 60 SR four reviews were rated "high", two were "moderate", one was "low" and 53 were "critically low". The mean AMSTAR 2 percentage score was 45.3% (standard deviation 22.6%) in a wide range from 7.1% to 93.8%. Predictors of higher quality were: type of review (higher quality in Cochrane Reviews), SR including only randomized trials and higher journal impact factor. Limitations: AMSTAR 2 is not intended to be used for the generation of a percentage score. Conclusions: According to AMSTAR 2 the overall methodological quality of SR on the treatment of adult major depression needs improvement. Although there is a high need for summarized information in the field of mental health, this work demonstrates the need to critically assess SR before using their findings. Better adherence to established reporting guidelines for SR is needed. Abstract : Public health; Epidemiology; Psychiatry; Depression; Evidence-based medicine; AMSTAR 2; Methodological quality; Risk of bias; Systematic review; Major depression.